Identification of a novel TOP2B::AFF2 fusion gene in B-cell acute lymphoblastic leukemia - Tao Liu; Yang Wang; Xi-Zhou An; Jiaqi Liu; Yuqin Wu; Yan Xiang; Yong-Jie Zhang; Lan Huang; Jia-Cheng Li; Yu-Zhuo-Pu Li; Jie Yu (Scientific Reports)
Abstract Genetic alterations play a pivotal role in leukemic clonal transformation, significantly influencing disease pathogenesis and clinical outcomes. Here, we report a novel fusion gene and investigate its pathogenic role in acute lymphoblastic leukemia (ALL). We engineer a transposon transfection system expressing the TOP2B::AFF2 transcript and introduce it into Ba/F3 cells. Functional studies, including proliferation, cell cycle, and apoptosis assays, were conducted to assess the fusion gene’s impact. In vitro assays reveal that the TOP2B::AFF2 fusion significantly enhances Ba/F3 cell proliferation and G1/S phase transition while suppressing differentiation and apoptosis. This study identifies TOP2B::AFF2 as a potential oncogenic driver. However, further validation through in vivo studies are warranted to fully elucidate the fusion gene’s role in leukemogenesis.